The Effect Of Service Quality And Product Excellence On Customer Satisfaction At The Sigma Motor Workshop In Lahat - Wahyu Darmawan; Mujari Mujari; Darwin Kesuma (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to determine the effect of service quality and product excellence on customer satisfaction, both partially and collectively, at the Sigma Motor Workshop. A sample of 67 consumers was taken using the accidental sampling technique. Based on the results of SPSS data processing, the resulting regression equation is as follows: Y = 5.816 + 0.748 X1 + 0.106 X2 + e. The coefficient of determination (r2) based on the SPSS data processing table is 0.715. This means that the customer satisfaction variable at the Sigma Motor Workshop can be explained by the service quality and product excellence variables, with a contribution of 71.5%, while the remaining 28.5% can be explained by other variables. The calculated F value is found to be greater than the F table (77.878 > 3.15). Thus, service quality and product excellence have a significant effect on customer satisfaction at the Sigma Motor Workshop. The service quality variable has a significant effect on customer satisfaction at the Sigma Motor Workshop, because the calculated t < from the t table or 9.592 > 1.998. The product excellence variable with calculated t < t table or 1.277 < 1.998 shows that there is no significant effect between product excellence on customer satisfaction at the Sigma Motor Workshop.